PG67 Acute surgical emergency patient (ASEP) simulation course. (10th November 2020) - Sait, Saif; Springbett, Peter; Hicks, Stephanie; Janakan, Gnananandan
Abstract : Introduction: Many surgical healthcare professionals feel inadequately prepared in dealing with acutely unwell surgical patients (1). Simulation can give doctors and nurses the confidence in managing these patients (2). Currently there is no high-fidelity simulation focusing on human factors in the field of surgery. Our aim was to run a full day interprofessional surgical simulation course for healthcare professionals. This is the only surgical interprofessional simulation currently being offered to healthcare professionals. Methods: We ran three full day interprofessional surgical simulation courses. Scenarios included managing acutely unwell surgical patients and being called when scrubbed in theatre. Each scenario had a surgical doctor and nurse, and this led to discussion on relevant human factors and clinical learning points. Results: Candidates who attended the course found that their confidence increased in managing acutely unwell surgical patients (4.5/10 to 8.2/10), doing an A-E assessment (6.6/10 to 8.4/10) and providing a good handover (6/10 to 8.3/10). Candidates rated the course as 9.6/10. Some of the comments from the course were 'teaching, excellent feedback in a safe environment' and 'much more confident in assessing and managing acutely unwell patients'. All the candidates who attended the course said that they would recommend this course to a colleague and felt it should be made available to all healthcare professionals. Discussion and Conclusion: This novel, high fidelity, interprofessional surgical simulation course was both well received and led to improved confidence in the management of acutely unwell surgical patients. The course allowed candidates to work in an interprofessional team. All the candidates would recommend this course to their colleagues. We would therefore recommend that this course be made available to all healthcare professionals working in surgery. References: Isherwood, J., Mughal, Z. and Yeung, J., 2013. Can simulation training improve foundation doctors' assessment and management of acutely unwell surgical patients?. BMJ, 346. Carling, J., 2010. Are graduate doctors adequately prepared to manage acutely unwell patients?. The clinical teacher ;7(2): pp.102–105.